CREACION DE UNA MICROEMPRESA DE RECICLADO DE BASURA ORGANICA, CON LOS ALUMNOS DE LA ESCUELA DE MEDICINA VETERINARIA Y ZOOTECNICA DE LA UNIVERSIDAD TECNICA DE CHIMBO, PROVINCIA BOLIVAR, COMO ALTERNATIVA DE AUTOGESTION. - ZOOT. VINICIO MONTALVO SILVA (2004)
CREATION OF AN ORGANIC WASTE RECYCLING MICROENTERPRISE, WITH STUDENTS FROM THE SCHOOL OF VETERINARY MEDICINE AND ZOOTECHNICS OF THE TECHNICAL UNIVERSITY OF CHIMBO, BOLIVAR PROVINCE, AS AN ALTERNATIVE FOR SELF-MANAGEMENT.